Green Ugi-3CR Method for the Synthesis of α-Aminoamides in Water Using SLS - Mirfattahi, Mahroo; Yazzaf, Rozita; Sayahi, Mohammad Hosein; Mahdavi, Mohammad (Current Organic Synthesis, 2025)
<span class=
Keywords: green chemistry principles